Factores biosociales y frecuencia de consumo de alcohol en el rendimiento académico de universitarios - Carranza Moreno, Sonia del Pilar (2019)
ABSTRACT Descriptive and correlational study, which aimed to determine the relationship between biosocial factors and the frequency of alcohol consumption, in academic performance. The sample consisted of 157 students from different faculties of the National University of Trujillo, to whom two instruments were applied: the first to identify biosocial factors and the second to identify the frequency of alcohol consumption. The information was processed and analyzed with the SPSS version 23 program and to determine the relationship between variables, the Chi-square statistical test was used. The results were: in biosocial factors; 68.1% of university students were 19 to 25 years old; 56% male; 59.2% only study and 44.6% have a nuclear family; on the frequency of alcohol consumption, 10.8% report an abuse frequency; 21% moderate consumption; 45.2% risky consumption frequency and 23% do not consume alcohol. It was evidenced that 78.8% have an average academic performance and moderate frequency of consumption; 67.6% average academic performance and risky consumption; 64.7% report average academic performance and abusive consumption, 58.3% with average academic performance and do not consume alcohol. It was concluded that there is no statistical link between biosocial factors with academic performance; however, there is a relation between the frequency of alcohol consumption and the academic performance of university students.